Publishing open-access bibliographical data on Ancient Greek and Latin texts: challenges, constraints, progression - Giovacchini, Julie; Capron, Laurent (Journal of data mining and digital humanities, 2021)
Version soumise et acceptée pour publication dans le JDMDH We present here both some of our thoughts on methodology in relation to the specific constraints that complexify the ways of structuring and accessing bibliographical data in the Sciences of Antiquity, and the solutions adopted by the IPhiS-CIRIS project for dealing with these constraints. The project began in 2014 in a general scientific environment that was still being standardised and structured, with digital bibliographical resources in this disciplinary field becoming increasingly numerous, although of uneven quality and hard to access and/or private.